2021
DOI: 10.1186/s12882-021-02244-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and subgroup analysis of the incidence of acute kidney injury (AKI) in patients with COVID-19

Abstract: Background Acute kidney injury (AKI) occurs among patients with coronavirus disease-19 (COVID-19) and has also been indicated to be associated with in-hospital mortality. Remdesivir has been authorized for the treatment of COVID-19. We conducted a systematic review to evaluate the incidence of AKI in hospitalized COVID-19 patients. The incidence of AKI in different subgroups was also investigated. Methods A thorough search was performed to find rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 57 publications
2
40
0
1
Order By: Relevance
“…The relative risk of serum creatinine elevation (RR 0.66; 95%CI 0.55–0.80; p < 0.001) was also lower in the remdesivir-treated group than the placebo. A systematic review and subgroup analysis by Xu et al [ 35 ] revealed that remdesivir did not increase the incidence of acute kidney injury in patients with COVID-19. Three RCTs [ 9 11 ] independently reported that a similar proportion of adverse effects occurred in the remdesivir and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk of serum creatinine elevation (RR 0.66; 95%CI 0.55–0.80; p < 0.001) was also lower in the remdesivir-treated group than the placebo. A systematic review and subgroup analysis by Xu et al [ 35 ] revealed that remdesivir did not increase the incidence of acute kidney injury in patients with COVID-19. Three RCTs [ 9 11 ] independently reported that a similar proportion of adverse effects occurred in the remdesivir and placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence is high (estimated to be 2–20% in hospitalized patients) and its mortality remains around 20% [ 251 ]. Of recent interest, AKI develops in 10% of hospitalized Covid-19 patients [ 254 ]. Beyond the acute phase, AKI was found to be associated with an 8.8-fold risk for CKD [ 255 ].…”
Section: Mrtf In Kidney Diseasesmentioning
confidence: 99%
“…Chan et al confirmed an AKI rate in COVID-19 patients of 7.58% (95% CI 3.30–13.54%) [ 12 ]. The recent meta-analysis of Xu et al showed that the frequency of AKI in COVID-19 patients lies somewhere around 10%, and that kidney damage is more frequent in older patients and patients suffering with a more acute form of the disease [ 13 ]. Putting all these factors together, these data led to the hypothesis that SARS-CoV-2 targets the kidney.…”
Section: Recent Findingsmentioning
confidence: 99%
“…It should also be noted that the AKI frequency in COVID-19 patients is of great concern. We and several other groups have observed an increased rate of AKI in patients with CKD history and in those suffering from other severe diseases [ 13 ]. Yet, none of this indicates a direct effect of COVID-19 on the kidneys.…”
Section: Pro and Contramentioning
confidence: 99%